MANAJEMEN RISIKO OPERASIONAL DAN PEMELIHARAAN TEMPAT PEMBUANGAN AKHIR (TPA) REGIONAL BANGLI DI KABUPATEN BANGLI - Wedana Yasa, I W; Sila Dharma, I G. B; Ketut Sudipta, I Gst (JURNAL SPEKTRAN, 2013)
To obtain the maximum and sustainable advantage it needs to carry out the operational and maintenance (OP) activities of TPA. It is necessary to maintain the Bangli Regional TPA so that it will give maximum and sustainable advantages. This study was aimed at identifying various major risks which may interfere with the TPA operating and maintenance so that mitigation can be done and to determine the risk ownership. The collected data were analyzed using descriptive qualitative method through the following stages: the risks were identified, the risks were evaluated, the risks were coped with, and the risk ownership could be identified. The risks identified totaled 72 consisting of: 9 (12.5%) risks which were under the unacceptable category, 16 (22.22%) risks which were under the acceptable category, and 1 (1.39%) risk which was under the negligible category. The major risks amounted to 55 risks (76.39%), included the obstacle to establishing the institution which was fully responsible for the operating and maintenance of the Bangli Regional TPA, the limited amounts of funds allocated by the central government, the provincial government, and the regency governments which were integrated into the Regional TPA, the obstacle to creating an affiliation between the government and the private institutions, and other risks. The risk mitigation was done by avoiding risks, reducing risks, and transferring risks starting from the institutional, regulation and financial aspects, and technical and non technical problems. Most risk ownerships were the responsibility of the Bangli Regional TPA management.
Keywords: TPA, operating and maintenance, risk mitigation